Beam combination schemes and technologies for the Planet Formation Imager - Pedretti, Ettore; Diener, Romina; Nayak, Abani Shankar; Tepper, Jan; Labadie, Lucas; Pertsch, Thomas; Nolte, Stefan; Minardi, Stefano (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We present the results of the technology developments which lead to the manufacturing of the first integrated optics 2-telescope ABCD unit and 4-telescope DBC component for L-band, mid infrared stellar interferometry. All the samples were manufactured with ultrafast laser inscription in Gallium Lanthanum Sulfide and were characterized in near field with monochromatic light at the wavelength of 3.39 μm. The choice of the laser writing parameters and the control of long range stresses arising from the manufacturing process are discussed taking in consideration the measured interferometric calibration data.
CRIS-Team Scopus Importer:2023-04-20
Keywords: fabrication and monochromatic characterization of laser-written multi-telescope combiners; Photonics-based mid-infrared interferometry II: Design